Ethics in the ambulatory business and entrepreneurship loans in Peru 2018 - Sarmiento Gamio, Enrique J. (2019)
At this time, in Peru, the notion of entrepreneurship has developed in different socioeconomic sectors. Of all of them, it highlights this fact in the migrant spaces and in the low resources.As a first option, ambulatory businesses were developed with the aim of growing in different sectors.This situation generates a modification in formal spaces, among them, the companies that dedicate themselves to make loans.In the following work, we seek to evaluate and study how these processes are developed in different companies ranging from banks to municipal savings banks. This study is not only from an economic view, but also sociological and anthropological, since it covers the dimensions of the idea that is handled by this type of entrepreneur and their social positioning.